Fourth-Semester Preservice Elementary Teachers’ Responses to Teaching Through Project-Based Learning: A Qualitative Study at Universitas Katolik Santo Thomas - Maria Sihotang (Pustaka Karya Mandiri, 2026)
Project-Based Learning (PjBL) has become increasingly relevant in teacher education because it provides preservice teachers with opportunities to connect pedagogical theory with practical learning experiences. Preservice elementary teachers need not only conceptual understanding of educational theories but also collaboration, communication, creativity, critical thinking, problem-solving, confidence, and professional readiness for future classroom practice. This study explores fourth-semester preservice elementary teachers’ responses to teaching through PjBL at Universitas Katolik Santo Thomas. The study employed a qualitative descriptive design involving 30 preservice elementary teachers. Data were collected through semi-structured interviews consisting of ten questions related to participants’ opinions about PjBL, understanding of course materials, perceived benefits, challenges, motivation, collaboration, critical thinking, problem-solving, lecturer facilitation, future implementation, and suggestions for improvement. The data were analyzed using thematic analysis by identifying repeated patterns across participant responses. The findings revealed eleven major themes: increased learning motivation, better understanding of course material, improved collaboration skills, enhanced communication skills, development of critical thinking, increased creativity, improved problem-solving skills, time management challenges, group coordination difficulties, positive perception of lecturer facilitation, and strong support for future PjBL implementation. The strongest theme was support for future PjBL implementation, appearing in 29 of 30 responses, followed by better understanding of course material and increased learning motivation. The findings indicate that preservice elementary teachers perceived PjBL as meaningful, practical, engaging, and professionally relevant. However, they also experienced challenges related to time management, group coordination, workload distribution, limited resources, and project planning. The study concludes that PjBL can strengthen preservice teachers’ professional learning when supported by clear instructions, structured project stages, lecturer feedback, peer assessment, consultation opportunities, and realistic project scheduling.